Analysis of Waiting Time, Quality of Care, and Accessibility of Services on Pregnant Women’s Satisfaction with Midwife Services at the Candi Community Health Center Sidoarjo Regency - Fadilatus Siriah; Novita Ana Anggraini; Indasah; Sentot Imam Suprapto; Atik Setiawan W (Jurnal Ragam Pengabdian, 2026)
Antenatal care (ANC) has an essential role in enhancing maternal health and lowering the maternal mortality rate (MMR) through the early identification of pregnancy-related risks. This study was conducted to examine the effects of waiting time, quality of care, and service accessibility on maternal satisfaction. A descriptive analytical study with a cross-sectional design was applied. The study involved 124 pregnant women who were randomly selected from a total population of 178 respondents. The research instrument consisted of a questionnaire, and data were analysed using bivariate tests and multivariate ordinal regression. The majority of respondents perceived waiting times as short (66.9%), service quality as good (70.2%), and service accessibility as high (68.5%). The level of satisfaction among pregnant women was predominantly in the ‘satisfied’ category (44.4%). The results of the multivariate ordinal regression analysis indicate that waiting time (p=0.000), quality of service (p=0.000) and accessibility of service (p=0.001) have a significant effect on the satisfaction of pregnant women (p < 0.05). Waiting time was the most dominant factor with a Wald value of 36.186. The efficiency of waiting time plays a crucial role in enhancing satisfaction as it relates to comfort and the perception of service quality. Good service quality and high accessibility also contribute to positive experiences for pregnant women, thereby encouraging the continued use of ANC services.